Teacher Education in Canada: Current State and Development Trends - N. V. Tikhonova (Moscow Polytechnic University, 2020)
During the last few years, higher education has been the subject of constant transformation, innovations and reforms. In response to the new demands of the society, universities increase academic mobility, attract international students, introduce information technologies and new approaches to learning: personalized learning, problem-based learning, flipped classroom, distance learning, blended learning and so on. The role of a teacher in introducing new educational technologies and preparing the future generation is of great importance, so the main priority all over the world is to improve the quality of teacher education.The purpose of this paper is to analyze the current state of initial teacher training in Canada, a country where a larger proportion of students performed at the highest levels of proficiency according to the most recent PISA study, which indicates the quality of teacher training. The paper discusses the main features of Canadian teacher education programs: the teacher education models, the program structure and duration, the program content as well as different methods for assessing student learning outcomes with particular attention paid to modern approaches to assessing the student professional competencies at Quebec teacher faculties. Based on a literature review, the results of comparative studies of Canadian researches as well as universities regulations and official websites information, we analyze the main trends in the teacher education in Canada.